Associations between body temperature and feed efficiency traits in lactating Holstein cows - Ligia Cavani; Larissa C. Novo; Faith S. Reyes; Bárbara M. Nascimento; Michael J. VandeHaar; Robert J. Tempelman; Kristen L. Parker Gaddis; Ransom L. Baldwin; José E.P. Santos; James E. Koltes; Heather M. White; Kent A. Weigel; et al. (JDS Communications)
Differences in feed efficiency among dairy cows could be partially explained by changes in body temperature due to the heat increment. This heat represents chemical energy lost, and theoretically, it should be lower in more efficient cows. The aim of this study was to investigate the associations between 3 body temperature traits, namely average body temperature, consistency of body temperature, and change in body temperature after the largest meal of the day, with 4 feed efficiency traits: DMI, milk energy, metabolic BW, and residual feed intake (RFI) in lactating Holstein cows. Data were collected from 1,068 mid-lactation Holstein cows enrolled in 36 feed efficiency trials from 2020 to 2023 at 5 research stations across the United States. Temperature records were obtained using an automatic temperature logger placed vaginally for 2 wk. Average body temperature was calculated as the individual mean, daily and over the 2-wk period, and consistency of body temperature was calculated as the log-transformed variance of the deviations of individual records from the cow's mean. Change in body temperature was calculated for a subset of cows that used the roughage intake control system (n = 278) and was defined as the difference in temperature after and before the largest meal of the day. Data for DMI, milk energy, metabolic BW, and RFI were collected from the same cows for 6 to 7 wk during the feeding trials. The associations between body temperature traits and feed efficiency traits were assessed using univariate linear regression models including cohort (trial-treatment), temperature-humidity index (THI), and the interaction between THI and research station as independent variables. Partial correlations between body temperature and feed efficiency traits controlling for cohort were calculated. Additionally, the importance of body temperature traits on RFI calculation was also evaluated. Increased body temperature was associated with cow that ate less and were lighter. Consistency of body temperature was negatively associated with DMI and milk energy, showing that greater variance in body temperature is linked to higher DMI and more milk energy. Smaller changes in body temperature after the largest meal were associated with lower DMI and milk energy. Adding body temperature traits to the RFI model did not change the coefficient of determination (adjusted R2), which remained ∼0.86. We found that cows that eat less have higher body temperatures, with less fluctuation throughout the day, compared with cows that consume more feed and produce more milk. Overall, our results suggest that vaginal temperature did not capture the heat increment expected in high RFI cows.